Apoptotic Gastritis in Melanoma Patients Treated With PD-1-Based Immune Checkpoint Inhibition – Clinical and Histopathological Findings Including the Diagnostic Value of Anti-Caspase-3 Immunohistochemistry - Placke, Jan-Malte; Rawitzer, Josefine; Reis, Henning; Rashidi-Alavijeh, Jassin; Livingstone, Elisabeth; Ugurel, Selma; Hadaschik, Eva; Griewank, Klaus; Schmid, Kurt Werner; Schadendorf, Dirk; Roesch, Alexander; Zimmer, Lisa (Frontiers in Oncology, 2021)
Background Gastritis induced by checkpoint inhibitors (CPI) is a rare but severe drug-related side effect. The reference standard for confirming CPI-associated gastritis (CPI-assGastritis) is histopathological assessment; however, the histopathological features of CPI-assGastritis are not yet adequately defined. Materials and Methods Gastric biopsies of melanoma patients with histopathologically suspected CPI-assGastritis were compared with gastric biopsies of patients with inflammation free gastric mucosa (IFGM), type A, B, and C gastritis with respect to apoptosis count and predominant histopathological features. Immunohistochemical anti-caspase-3 staining was performed to identify apoptosis. Quantification was performed by manually counting the number of apoptotic events per 10 high-power fields (HPF). Clinical symptoms, treatment, and follow-up data of patients with CPI-assGastritis were examined. The nonparametric Mann–Whitney U test was used for statistical testing. Results Five melanoma patients (three women, two men; median age: 45 years) were treated with PD-1-based CPI. The patients reported epigastric pain, weight loss, nausea, and vomiting. Histologically, the patients with CPI-assGastritis showed a partly lymphocytic, partly granulocytic inflammatory infiltrate. Manual counting of apoptotic cells in biopsy tissue slides stained against caspase 3 revealed a median of 6 apoptotic events/10 HPF (95% CI, 2.75-17.30) in the patients with CPI-assGastritis. Results for the comparison cohort (patients n = 21) were a median of 1 apoptotic event/10 HPF (95% CI, 0.5–4.5) for type-A gastritis (six patients), a median of 2 apoptotic events/10 HPF (95% CI, 0–4.5) for type-B gastritis (five patients), and no apoptosis for IFGM and type-C gastritis (five patients). Patients with CPI-assGastritis had a significantly higher apoptosis count than patients with IFGM (p<0.01), type A (p<0.05), B (p<0.05), and C gastritis (p<0.01). None of the CPI-assGastritis biopsies showed evidence of Helicobacter pylori. All CPI-assGastritis patients responded to systemic treatment with corticosteroids. Conclusion CPI-assGastritis manifests with nonspecific symptoms but histologically shows a high number of apoptotic events, which can best be visualized by anti-caspase-3 immunohistochemistry. This histopathological feature may help to histologically differentiate CPI-assGastritis from other forms of gastritis and inform decision-making regarding its optimal management.